If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2j + y = 60 Solving 2j + y = 60 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-1y' to each side of the equation. 2j + y + -1y = 60 + -1y Combine like terms: y + -1y = 0 2j + 0 = 60 + -1y 2j = 60 + -1y Divide each side by '2'. j = 30 + -0.5y Simplifying j = 30 + -0.5y
| 11x+9=11x+18 | | (1+x)=0.4535 | | Mn-m^2n+mn^2=0 | | (3a-7b)-(4a-b)= | | 4*2+11X-4=0 | | -8(r+-2)=40 | | =-25x^2+40x-16 | | 2()=3x-9 | | =3x-9/2 | | -9k^2+24k-16=0 | | 5-2x=8x-9 | | 9x^2+4y^2=36z^2 | | X^3-9x^2+25x=0 | | 12=x+16 | | x-1=2y-10 | | 12a-1=-a+25 | | x^3=8 | | 7(11x+1)=77x-5 | | 5t-16=t | | sin(x-100)=-0.3 | | 8x-125=931 | | g-(h-2g)= | | x-2y=68 | | 3(a-1)=69 | | (u+2)*8=40 | | 18=x*x | | 2x-3y=x-2y | | 2j+10=2 | | w+7=32 | | 16=-8(5p+8) | | 300+3x-50= | | 8(10n+7)=n+56 |